PROSEDUR PENYELENGGARAAN PENGATUR ACARA PERNIKAHAN (WEDDING ORGANIZER) PADA AFFAY PROJECT DI KOTA SUKABUMI - Lia Liliawati; Rahyang Rizal; Markus Fajar Nugroho (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2022)
This study aims to determine the procedure for organizing a wedding ceremony at the Affay Project in Sukabumi City. To find out the obstacles and solutions faced in the procedure for organizing a wedding ceremony at the Affay Project in Sukabumi City. This research method uses Direct Observation (Observation), interviews and literature study. In this study, the authors analyzed the data descriptively, namely only seeing, describing a phenomenon that is currently happening in the procedures for organizing the Wedding Event Project in Sukabumi City. The results of this study indicate that the procedures for organizing wedding arrangements at the Affay Project are not in accordance with the procedures, including in the event section, the equipment section and the implementation section. The solution to the constraints on the implementation of the marriage organizer is the solutions that the authors conclude, namely the Affay Project to add volunteer human resources or to let it be overwhelmed to minimize double jobs. The Affay Project makes 2 plans in the arrangement of the events and the Affay Project asks the consumer, namely the bride and groom and their family, to take the time to double-check the wedding package order to minimize the sudden addition or reduction of equipment